The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00415-005-0605-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Babinski Sign in Brain Death

Abstract: Sirs: The early criteria for brain death (BD) included the absence of all nervous system functions (i. e. cerebral and spinal death) [1]. However, the demonstration of spinal reflexes in brain-dead patients [2, 5-8, 12, 13] led to revision of the criteria and acceptance of these reflexes as compatible with the diagnosis of BD [10]. Although the first studies noted that the Babinski sign was not observed in BD [7, 8], reviews still state that it may be present [10, 15]. We studied the characteristics of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…[16][17][18][19][20][21] One Class III study of 144 patients pronounced brain dead found 55% (95% confidence interval [CI] 47-63) of patients had retained plantar reflexes, either flexion or "stimulation induced undulating toe flexion." 22 Another study documented plantar flexion and flexion synergy bilaterally that persisted for 32 hours after the determination of brain death. 23 Two Class III studies suggested that the ventilator may sense small changes in tubing pressure and provide a breath that could suggest breathing effort by the patient where none exists.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…[16][17][18][19][20][21] One Class III study of 144 patients pronounced brain dead found 55% (95% confidence interval [CI] 47-63) of patients had retained plantar reflexes, either flexion or "stimulation induced undulating toe flexion." 22 Another study documented plantar flexion and flexion synergy bilaterally that persisted for 32 hours after the determination of brain death. 23 Two Class III studies suggested that the ventilator may sense small changes in tubing pressure and provide a breath that could suggest breathing effort by the patient where none exists.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…However, since this comprehensive guideline became known, studies have largely focused on specific neurologic manifestations or type of confirmatory tests. [5][6][7] No detailed studies as yet have been published on actual hospital practice in a large number of patients pronounced brain dead. A review could identify concerns in key areas such as correctly followed procedures, physician involvement, and apnea testing.…”
mentioning
confidence: 98%
“…Mittels wiederholter Berührung der Kornea von der Seite mit einem Wattestäbchen wird der Versuch unternommen, einen [51]. Spontane, spinal-motorische Extremitätenbewegungen nach Hirnfunktionsausfall werden auch als Lazarus-Phänomen bezeichnet (nach der biblischen Geschichte von der Wiedererweckung des toten Lazarus durch Jesus).…”
Section: Prüfung Des Kornealreflexesunclassified